Hysteresis in ocean export production owing to CO2 forcing - Jieun Wie; Byung-Kwon Moon (Scientific Reports)
Abstract To mitigate global warming, reducing greenhouse gases is crucial. While ocean meridional overturning circulation, dissolved oxygen, and sea surface temperature are irreversible despite CO2 reductions, the irreversibility of ocean export production is less understood. This study examines this phenomenon using CO2 removal scenarios in the LOVECLIM model. The experiment quadrupled CO2 from 367 ppm over 140 years at 1% per year, then decreased it at the same rate, followed by a 5,000-year restoration period. The ocean export production decreased in the tropics and North Atlantic but increased in polar regions. Production lagged in response to CO2 changes, being more pronounced during the decrease. The key factors include rising ocean temperatures, melting sea ice, and weakened global ocean circulation. Recovery periods can last up to 1,300 years globally, particularly in the Southern Ocean, with shorter periods in the tropics and North Atlantic. The Southern Ocean requires special attention owing to its long-term changes.